Binder-Free Zinc–Iron Oxide as a High-Performance Negative Electrode Material for Pseudocapacitors - Qasim Abbas; Abdul Mateen; Abdul Jabbar Khan; Gaber E. Eldesoky; Asim Idrees; Awais Ahmad; Elsayed Tag Eldin; Himadri Tanaya Das; Muhammad Sajjad; Muhammad Sufyan Javed (Nanomaterials, 2022)
The interaction between cathode and anode materials is critical for developing a high-performance asymmetric supercapacitor (SC). Significant advances have been made for cathode materials, while the anode is comparatively less explored for SC applications. Herein, we proposed a high-performance binder-free anode material composed of two-dimensional ZnFe2O4 nanoflakes supported on carbon cloth (ZFO-NF@CC). The electrochemical performance of ZFO-NF@CC as an anode material for supercapacitor application was examined in a KOH solution via a three-electrode configuration. The ZFO-NF@CC electrode demonstrated a specific capacitance of 509 F g−1 at 1.5 A g−1 and was retained 94.2% after 10,000 GCD cycles. The ZFO-NF@CC electrode showed exceptional charge storage properties by attaining high pseudocapacitive-type storage. Furthermore, an asymmetric SC device was fabricated using ZFO-NF@CC as an anode and activated carbon on CC (AC@CC) as a cathode with a KOH-based aqueous electrolyte (ZFO-NF@CC||AC@CC). The ZFO-NF@CC||AC@CC yielded a high specific capacitance of 122.2 F g−1 at a current density of 2 A g−1, a high energy density of 55.044 Wh kg−1 at a power density of 1801.44 W kg−1, with a remarkable retention rate of 96.5% even after 4000 cycles was attained. Thus, our results showed that the enhanced electrochemical performance of ZFO-NF@CC used as an anode in high-performance SC applications can open new research directions for replacing carbon-based anode materials.